Challenges for the academic spin-offs in Mexico as a result of the economic valorization of RD & I from the universities - Maldonado-Sada, María Teresa (Universidad Autónoma de Tamaulipas, 2019)
The economic valorization model from the Research Development and Innovation (RD & I) for higher education  research  results  through the creation of spin-offs, has demonstrated to attain a high success index and a positive social impact in several countries. Accordingly, Latin American Universities are encouraging an entrepreneurship culture for the creation of spin-offs since it leads to economic profits for both, the University and the participating researchers. The objective of this paper was to analyze the national and international context of academic spin-offs in order to identify some factors that promote or prevent their creation and success as strategy to accelerate their implementation in Mexico. Since this model has recently been introduced to the country, academic spin-offs require the creation of a new legal framework inside the universities in order to achieve two main goals: one is to establish clearly the rights and responsibilities of the institution and the participants, and the second one entails fostering their management, implementation and development. In addition, there is similarly a need to channel the RD & I results in order to transform them into marketable goods; to train researchers in entrepreneurship and intellectual property; increase private research investment, and generate policies and conditions to increase the number of researchers in Mexico.